2022
DOI: 10.1002/adhm.202200626
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Skulls With Integrated Transparent Electrode Arrays for Cortex‐Wide Opto‐Electrophysiological Recordings

Abstract: Electrophysiology and optical imaging provide complementary neural sensing capabilities – electrophysiological recordings have high temporal resolution, while optical imaging allows recording of genetically‐defined populations at high spatial resolution. Combining these two modalities for simultaneous large‐scale, multimodal sensing of neural activity across multiple brain regions can be very powerful. Here, transparent, inkjet‐printed electrode arrays with outstanding optical and electrical properties are sea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 77 publications
(121 reference statements)
2
20
0
Order By: Relevance
“…In another example, Donaldson et al demonstrated transparent PEDOT:PSS MEA for simultaneous electrical and optical recording of cortical dynamics from multiple brain regions. 122 The patterning and fabrication of the MEA relied on inkjet printing of Ag interconnects and bond pads and 200 nm thick PEDOT:PSS microelectrodes (50 μm in diameter) on laser patterned PET substrates, followed by parylene C encapsulation. The 10 microelectrodes in the MEA spread over a window with a large field of view of ∼45 mm 2 for simultaneous optical imaging.…”
Section: Soft Transparent Meas For Neural and Cardiac Applicationsmentioning
confidence: 99%
“…In another example, Donaldson et al demonstrated transparent PEDOT:PSS MEA for simultaneous electrical and optical recording of cortical dynamics from multiple brain regions. 122 The patterning and fabrication of the MEA relied on inkjet printing of Ag interconnects and bond pads and 200 nm thick PEDOT:PSS microelectrodes (50 μm in diameter) on laser patterned PET substrates, followed by parylene C encapsulation. The 10 microelectrodes in the MEA spread over a window with a large field of view of ∼45 mm 2 for simultaneous optical imaging.…”
Section: Soft Transparent Meas For Neural and Cardiac Applicationsmentioning
confidence: 99%
“…Instead, the observed neural signal is a population summation of the activity within essentially a 3-dimensional voxel (not just 2 dimensional) that includes the dendrites, somata, and axons within that volume. While typical wide-field Ca 2+ imaging does not report the activity of single cells, there are strategies, such as sparse expression of indicators and/or restriction to the soma, that can provide single cell resolution [ 76 , 77 ].…”
Section: Limitations Of Wide-field Imagingmentioning
confidence: 99%
“…However, chronic studies with transparent ECoG electrodes have been restricted to a single brain region and a small fields of view (~2–5 mm 2 ). To address this limited field of view, transparent, inkjet-printed electrode arrays have been integrated into morphologically conformant transparent polymer skulls (eSee-Shells) [ 77 ]. The electrodes and interconnects are composed of poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), a transparent, printable conductor with excellent electrical properties.…”
Section: New Developmentsmentioning
confidence: 99%
“…Microelectrode arrays made of graphene or carbon nanotubes on transparent parylene C or other substrates have been employed in combination with single- and multiphoton optical imaging in vivo by us and others (Driscoll et al 2021, Kuzum et al 2014, Lu et al 2018, Park et al 2016, Park et al 2014, Thunemann et al 2018, Zhang et al 2018). The second strategy is using non-transparent metal and polymer electrodes on a transparent substrate, where the electrodes are small enough not to produce significant shadows (Donahue et al 2018, Donaldson et al 2022, Ganji et al 2018, Ganji et al 2019, Hossain et al 2020, Qiang et al 2018, Seo et al 2019). Following the second strategy, we have previously developed stable and biocompatible Poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) surface electrode arrays suitable for chronic implantation (Ganji et al 2018, Ganji et al 2019, Hossain et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 3, 2022. ; https://doi.org/10.1101/2022.09.01.506113 doi: bioRxiv preprint 6 transparent metal and polymer electrodes on a transparent substrate, where the electrodes are small enough not to produce significant shadows (Donahue et al 2018, Donaldson et al 2022, Ganji et al 2018, Hossain et al 2020, Qiang et al 2018, Seo et al 2019. Following the second strategy, we have previously developed stable and biocompatible Poly(3,4ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) surface electrode arrays suitable for chronic implantation (Ganji et al 2018, Hossain et al 2020.…”
Section: Introductionmentioning
confidence: 99%